Technology adoption and innovation: The establishment of airmail and aviation innovation in the United States , 1918–1935 - Sohn, Eunhee; Seamans, Robert; Sands, Daniel B. (Strategic Management Journal, 2024)
Abstract Research Summary This article explores how technology adoption can shape innovative activity. We study this issue within the historical context of the introduction and expansion of airmail across the United States between 1918 and 1935 using archival material and a novel dataset of early 20th century patents. A joint qualitative and quantitative investigation indicates that local individual and corporate actors applied diverse pools of knowledge and intensified their work with aviation innovations following airmail entry into their county. Moreover, we find evidence that the co‐location of aircraft manufacturing and airmail operations was associated with more corporate innovations that facilitated economies of scale and corresponded to increased technological diversification of firms' aviation patent portfolios. Ultimately, this paper deepens our understanding of the antecedents, consequences, and organizational processes that underpin innovation. Managerial Summary This research investigates how aviation innovation in the United States was influenced by the postal service's early 20th century introduction and expansion of airmail routes. Our results indicate that counties with an airmail route experienced increased aviation‐related patenting by individual and corporate inventors relative to similar counties that did not receive an airmail route. Moreover, we find that corporate inventors working in airmail counties that also contained aircraft manufacturers were particularly active in technological areas that enhanced aircraft economies of scale and patented in a wider range of aviation‐related domains. An implication of this work for managers and policymakers is that early access to nascent technology can be a driver of local innovation and that spillovers can benefit diverse economic actors working in close proximity.